2012
DOI: 10.1074/mcp.m111.016121
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Produces Immunosuppressive Effects in Nonhuman Primates at the Proteomic and Cellular Levels

Abstract: Morphine has long been known to have immunosuppressive properties in vivo, but the molecular and immunologic changes induced by it are incompletely understood. To explore how these changes interact with lentiviral infections in vivo, animals from two nonhuman primate species (African green monkeys and pigtailed macaques) were provided morphine and studied using a systems biology approach. Biological specimens were obtained from multiple sources (e.g. lymph node, colon, cerebrospinal fluid, and peripheral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 76 publications
1
42
0
Order By: Relevance
“…Firstly, certain DOA are associated with immunosuppressive effect, rendering drug users more prone to virus infection. Studies have found that morphine suppressed T cell activation in the lymph node, paralleled with a decrease in activation levels of T cells in peripheral blood in nonhuman primates [126]. Methamphetamine has been shown to accelerate the premature demise of activated T cells [127], and reduce the number of dendritic cells and natural killer cells [128,129].…”
Section: Autophagy In Hiv-1 With Co-exposure Of Doamentioning
confidence: 99%
“…Firstly, certain DOA are associated with immunosuppressive effect, rendering drug users more prone to virus infection. Studies have found that morphine suppressed T cell activation in the lymph node, paralleled with a decrease in activation levels of T cells in peripheral blood in nonhuman primates [126]. Methamphetamine has been shown to accelerate the premature demise of activated T cells [127], and reduce the number of dendritic cells and natural killer cells [128,129].…”
Section: Autophagy In Hiv-1 With Co-exposure Of Doamentioning
confidence: 99%
“…HeLa cells were disrupted, and proteins were tryptically digested, phosphopeptide enriched, TMT10 labeled, and high mass accuracy LC-MS/MS analyzed as previously described (47). Variations include use of TMT10 instead of iTRAQ labeling, cell lysate vs. tissue disruption, and use of Q Exactive Orbitrap MS. HEK293 cell LC-MS/MS analyses were performed identically, except for quantitation that used label-free approaches as previously described (48).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, morphine is widely used for clinical analgesic therapy and has very important medical value. However, morphine has immunosuppressive properties and affects the immune system, including T lymphocytes, B lymphocytes, natural killer cells, macrophages, and mononuclear phagocytes (Brown et al, 2012;Abellan et al, 2014). Pain generally leads to immune suppression, which is attenuated by morphine; however, but morphine also has immunosuppressive properties that should not be ignored.…”
Section: Groupmentioning
confidence: 99%